2020
DOI: 10.1021/acs.langmuir.0c00103
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Fluorescent HIV Capsid Spheres for Detection of Capsid Binders

Abstract: The human immunodeficiency virus (HIV) capsid is a coneshaped capsule formed from the viral capsid protein (CA), which is arranged into a lattice of hexamers and pentamers. The capsid comprises multiple binding interfaces for the recruitment of host proteins and macromolecules used by the virus to establish infection. Here, we coassembled CA proteins engineered for pentamer cross-linking and fluorescence labeling, into spherical particles. The CA spheres, which resemble the pentamer-rich structure of the end c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Beyond that, the pentamers localized towards the ends of the cone might also guide the perpendicular orientation of HIV-1 capsids with respect to NPCs during docking, and it may be hypothesized that preferential binding of the narrow ends to the NPC is mediated by the stronger enrichment of pentamers in this area of the cone. In a recent report (Lau et al, 2020), the authors established an in vitro system of self-assembled CA N21C/A22C (Pornillos et al, 2011) spheres, which adopted the same pentamer−hexamer and hexamer−hexamer interaction interfaces as found in the highly curved ends of the HIV capsids. They showed that CypA binds to those regions with a higher stoichiometry than to the tubular hexameric lattice and hypothesized that CA pentamers might represent specialized binding sites that are recognized by cyclophilin domains contained in host proteins, such as CypA and NUP358.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, the pentamers localized towards the ends of the cone might also guide the perpendicular orientation of HIV-1 capsids with respect to NPCs during docking, and it may be hypothesized that preferential binding of the narrow ends to the NPC is mediated by the stronger enrichment of pentamers in this area of the cone. In a recent report (Lau et al, 2020), the authors established an in vitro system of self-assembled CA N21C/A22C (Pornillos et al, 2011) spheres, which adopted the same pentamer−hexamer and hexamer−hexamer interaction interfaces as found in the highly curved ends of the HIV capsids. They showed that CypA binds to those regions with a higher stoichiometry than to the tubular hexameric lattice and hypothesized that CA pentamers might represent specialized binding sites that are recognized by cyclophilin domains contained in host proteins, such as CypA and NUP358.…”
Section: Discussionmentioning
confidence: 99%
“…Using TCCD, we determined the intensity ratio for cofactors CypA-AF488, CPSF6-AF488 or F-dATP interacting with capsid added in a large molar excess to the binding reaction ( Fig 4D, also see Supporting Fig S3C for hexahistidine-tagged CypA labelled with tris-NTA-AF488). The analyte:CA intensity ratio determined for CypA-AF488 was about 5-fold larger than for CPSF6-AF488, reflecting the differences in affinity (KD of ~10 μM for CypA 16,22,23,40,44 and ~50 μM for CPSF6 14 ). The low intensity ratio determined for F-dATP reflects both the lower number of binding sites on the capsid (1 pore per CA hexamer) as well as the lower emission of photons by fluorescein compared to AF488.…”
Section: Two-color Coincidence Detection Of Fluorescent Analytes and mentioning
confidence: 89%
“…Labelled capsids were produced by co-assembly of CA A204C and CA K158C-AF568 (76 μM:4 μM) as above, yielding particles with an estimated label fraction of 2.5% due to the lower assembly efficiency of labeled CA K158C. 22,23 For affinity measurements, assembled particles were collected by centrifugation (18000 g, 10 min, 4°C) and resuspended in 50 mM Tris, pH 8, 1M NaCl to remove unassembled CA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations